2014
DOI: 10.1177/1933719113492212
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Trimethylation of Histone H3 Mediates Impaired Expression of Hepatic Glucose 6-Phosphatase Expression in Offspring From Rat Dams Exposed to Hypoxia During Pregnancy

Abstract: Given that hepatic glucose 6-phosphatase (G6Pase, involved in gluconeogenesis) has been demonstrated to be altered long term in animal models of intrauterine growth restriction (IUGR), we hypothesized that hypoxia in utero may regulate G6Pase expression via epigenetic mechanisms. To address this further, a rat model of maternal hypoxia leading to IUGR and impaired liver growth was utilized. In the 12-month-old male offspring of pregnant rat dams exposed to 11.5% atmospheric oxygen from gestational day (gd) 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Hypoxic history enhances the mRNA level of gluconeogenic and glucose-transport-related genes in juvenile trout Apart from perinatal nutrition, fetal hypoxia is one of the most extensively studied environmental factors able to induce long-term metabolic changes in mammals (Myatt, 2006;Seckl and Holmes, 2007). Several studies in both mammals and teleost species showed that hypoxia exposure during early life can affect growth and glucose metabolism in adulthood (Camm et al, 2011;Osumek et al, 2014;Vanderplancke et al, 2015). In the present study, a subtle but significant increase in feed efficiency in weeks 19-24 was found in juveniles with a hypoxic history compared with those with a normoxic history.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxic history enhances the mRNA level of gluconeogenic and glucose-transport-related genes in juvenile trout Apart from perinatal nutrition, fetal hypoxia is one of the most extensively studied environmental factors able to induce long-term metabolic changes in mammals (Myatt, 2006;Seckl and Holmes, 2007). Several studies in both mammals and teleost species showed that hypoxia exposure during early life can affect growth and glucose metabolism in adulthood (Camm et al, 2011;Osumek et al, 2014;Vanderplancke et al, 2015). In the present study, a subtle but significant increase in feed efficiency in weeks 19-24 was found in juveniles with a hypoxic history compared with those with a normoxic history.…”
Section: Discussionmentioning
confidence: 99%
“…through embryonic hypoxia exposure (Liu et al, 2017). Indeed, hypoxia is a favourable stimulus candidate when investigating glucosemetabolism programming because hypoxia is known to affect hepatic glucose utilisation (Osumek et al, 2014;Zhong and Mostoslavsky, 2010). Moreover, such a stimulus can be easily applied before first feeding.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies demonstrate that exposure to hypoxia can alter the epigenetic landscape at the chromatin level in cells [14,16,[64][65][66][67][68][69][70] (Table 3). Similar changes to epigenetic marks, including histone lysine methylation, have been observed in development and in disease states where hypoxia is known to be an important feature.…”
Section: Histone Methylation and Hypoxiamentioning
confidence: 99%
“…Indeed, in the light of our results during ontogenesis, it would be a good option to apply a stimulus around or before stages 22/23 in order to affect the expression of glucose metabolismrelated genes, as mRNA levels of all genes increased during this period of development. A hypoxic stimulus could be of interest in this context as hypoxia is known to affect glucose metabolism (Osumek et al, 2014;Zhong and Mostoslavsky, 2010).…”
Section: New Tools For Programming Investigationmentioning
confidence: 99%
“…In order to impact on this metabolism in the long term, another window of plasticity has to be defined before the first feeding period. However, such an investigation entails considering a non-nutritional stimulus such as hypoxia, known to affect glucose metabolism (Osumek et al, 2014;Zhong and Mostoslavsky, 2010), and having greater understanding of the transcription patterns of glucose metabolism-related genes during ontogenesis and before nutritional transition. Previous studies carried out in zebrafish (Rocha et al, 2013(Rocha et al, , 2015 have revealed that metabolic programming could occur following a nonnutritional stimulus such as nutrient injection, applied during late embryogenesis and before first feeding.…”
Section: New Tools For Programming Investigationmentioning
confidence: 99%